Kemampuan Pemecahan Masalah Open Ended pada Materi Bangun Datar Segiempat dan Segitiga Siswa Kelas VII SMPN 1 Gunungsari - Pegi Listiani; Nani Kurniati; Junaidi Junaidi; Nurul Hikmah (Griya Journal of Mathematics Education and Application, 2022)
This study aims to describe the level of students’ open-ended problem-solving skills in solving math problems based on Polya’s steps on the material of quadrilaterals and triangles for class VII SMPN 1 Gunungsari in the 2021/2022 school year. The type of research used in descriptive research. The research subjects were 20 students who were selected with a sampling technique using a promotional start. The data collection techniques use tests and interviews. The results of the study were students with high abilities were able to fulfill every step Polya, students with moderate abilities had not been able to fulfill the fourth stage, namely reviewing the results that had been obtained, and students with low abilities had not been able to carry out the three stages of problem-solving, namely understanding the problem, thinking about plans. And looking back. Overall, the average ability of students in solving open-ended math problems based on Polya’s steps is in the medium category. The majority of students have not been able to write down what is known, what was asked and have not been able to re-examine the results obtained